LOW FLOW HYDROLOGY: A REVIEW - Smakhtin V.U. (My University, 2001)
The paper intends to review the current status of low-flow hydrology - a discipline which deals with minimum flow in a river during the dry periods of the year. The discussion starts with the analysis of low-flow generating mechanisms operating in natural conditions and the description of anthropogenic factors which directly or indirectly affect low flows. This is followed by the review of existing methods of low-flow estimation from streamflow time-series, which include flow duration curves, frequency analysis of extreme low-flow events and continuous low-flow intervals, baseflow separation and characterisation of streamflow recessions. The paper describes the variety of low-flow characteristics (indices) and their applications. A separate section illustrates the relationships between low-flow characteristics. The paper further focuses on the techniques for low-flow estimation in ungauged river catchments, which include a regional regression approach, graphical representation of low-flow characteristics, construction of regional curves for low-flow prediction and application of time-series simulation methods. The paper presents a summary of recent international low-flow related research initiatives. Specific applications of low-flow data in river ecology studies and environmental flow management as well as the problem of changing minimum river flows as the result of climate variability are also discussed. The review is largely based on the research results reported during the last twenty years.
Keywords: LOW FLOW; DROUGHT; FLOW DURATION CURVE; LOW-FLOW FREQUENCY; LOW-FLOW SPELLS; RECESSIONS; BASEFLOW; REGRESSION; MODELLING; FRESHWATER ECOLOGY